Amnesia Interrupted: Re-Membering the Living Past in Feminist Theory and Suzanne Lacy’s Crystal Quilt - Basting, Anne Davis (Journal of Dramatic Theory and Criticism, 1996)
Amnesia Interrupted: Re-Membering the Living Past in Feminist Theory and Suzanne Lacy’s Crystal Quilt